2005
DOI: 10.1360/062005-127
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation at the JK locus causing Jknull phenotype in a Chinese family

Abstract: Urea transporters are a group of proteins that facilitate urea movement across biological membranes. Kidd blood group (Jk antigen) and urea transporter of human erythrocytes are carried by the same protein UT-B. To investigate the molecular basis of the Jk null phenotype in the Chinese population, blood samples from Chinese individuals were screened using the 2 mol/L urea solution hemolysis test. Urea and water permeability of erythrocytes membrane was measured by stopped-flow light scattering. Genomic DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…UT-B protein expressed in the human erythrocyte is identified as the Jk antigen [5] . Jk (a-b-) (Jk null ) humans, who are very rare, have a mild urine-concentrating defect [6,7] . It has not been reported that Jk null individuals are associated with any other clinical syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…UT-B protein expressed in the human erythrocyte is identified as the Jk antigen [5] . Jk (a-b-) (Jk null ) humans, who are very rare, have a mild urine-concentrating defect [6,7] . It has not been reported that Jk null individuals are associated with any other clinical syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This rare phenotype has been reported with the highest frequency in Polynesians (0·1–1·4%). In the Chinese populations, the frequency of JK(a‐b‐) in the southern regions is about 1:5000 (10/50 000 in Guangzhou), which is higher than some other reported regions (1:20 000 in Changchun ; 1:25 000 (4/102 760 and 2/48 400) in Shanghai ; 1:17000–1:20 000 (3/52 260 to 2/40 337 ) in Nanjing; not found (0/23 909) in Zhejiang ) using the red blood cell urea lysis resistance assay for screening. Several patients with anti‐Jk3 were also encountered in Guangzhou .…”
Section: Genotyping Studies For the Null Phenotypes Of Rbcsmentioning
confidence: 66%
“…The permeation of water through UT-B, although initially controversial (Martial et al 1996; Sidoux-Walter et al 1999), has since been well established (Yang and Verkman 1998; Yang and Verkman 2002; Meng et al 2005). Recent estimates of the rate of water permeation through UT-B are similar to those measured for aquaporins (Azouzi et al 2013).…”
Section: 4 Interactions With Ligands and The Structural Basis Of mentioning
confidence: 99%